An environmental concentration of aged microplastics with adsorbed silver significantly affects aquatic organisms. (15th May 2020) - Kalčíková, Gabriela; Skalar, Tina; Marolt, Gregor; Jemec Kokalj, Anita
Abstract: Microplastics are very complex pollutants; they can be made of many polymer types and exist in various shapes and sizes. When they enter the environment they are affected by biotic and abiotic factors that cause their properties to change. In this context, the aim of our study was to evaluate the extent to which biofouling affects the properties and toxicity of microplastics. Cosmetic polyethylene microbeads were incubated in stream water for four weeks resulting in biofouling and aging. Subsequently, the changes in properties (sinking, particle size, adsorption, and leaching of model metal – silver) and the microplastics toxicity to daphnids Daphnia magn a and duckweed Lemna minor were evaluated. Pristine microplastics did not affect daphnids but they significantly affected the root growth of duckweed. On the other hand, reference natural particles (beech sawdust) did not show any negative effects. We observed significant differences in the properties of aged versus pristine microplastics. When compared to pristine microplastics, aged microplastics adsorbed more silver and the subsequent leaching of silver was more intensive, especially in the medium with an acidic pH. Microplastics with adsorbed silver had a high ecotoxicological potential and at environmentally relevant concentrations affected both daphnids and duckweed. This study suggests that biofouling is an important parameter that affects microplastics properties, pollutant adsorption and release into the environment, and toxicity. Overall, there are significant alterations of the microplastics properties, behaviour, and fate in the environment. Graphical abstract: Image 1 Highlights: Biofouling (aging) of microplastics (MPs) significantly alters their properties. Adsorption of Ag and its leaching is enhanced on MPs with a biofilm. Environmentally relevant concentrations of aged MPs with Ag affect organisms. MPs with adsorbed silver had high ecotoxicological potential.